PERANCANGAN DAN PENERAPAN APLIKASI PENJUALAN DENGAN QR CODE MENGGUNAKAN METODE RAD - Siregar, Lestari; Annurrullah Fajrin, Alfannisa (Computer Science and Industrial Engineering, 2025)
The swift advancement of information technology has changed how businesses conduct their operations, particularly in the sales process. This research centers on designing and implementing a web-based sales application utilizing QR Code at PT. Megah Jaya Sakti, a company operating in the building materials industry. Although the company still employs conventional sales methods, there is an urgent need to enhance the efficiency and accuracy of transaction recording. QR Code, as a technology capable of storing information quickly and practically, is expected to facilitate product identification and transaction verification. Designing and developing a sales application that streamlines transaction management, utilizing QR Code technology for transaction identification and verification, and accelerating the application development process through the use of the Rapid Application Development (RAD) method are the goals of this study. The RAD method is chosen for its focus on speed and flexibility, allowing for the early testing of QR Code features during development. The results of this research are expected to provide an efficient and accurate solution for transaction management at PT. Megah Jaya Sakti, as well enchance customer satisfaction through a faster and more modern transaction process.